Hari TUHAN sebagai Momentum Penghakiman dan Pemulihan: Studi Eskatologis Amos 5:18–24 (International Forum of Researchers and Lecturers, 2025)
The concept of the Day of the LORD in the prophetic tradition of the Old Testament is often narrowly understood as a day of victory and salvation for Israel. However, the book of Amos offers a sharp critique of such an interpretation. This study aims to examine the eschatological meaning of the Day of the LORD in Amos 5:18–24 as a moment of judgment and restoration. This research employs a qualitative method with a biblical hermeneutical approach, particularly historical-contextual and theological analysis of Amos 5:18–24. The findings indicate that the Day of the LORD is portrayed as a divine event that brings judgment against social injustice, religious hypocrisy, and ethical deviation among the people of Israel. At the same time, the text opens the possibility of restoration through the demand for justice and righteousness as expressions of true worship. Therefore, Amos’s eschatology is not speculative about the future but functions as a prophetic critique that calls for repentance and social transformation. This study affirms that the Day of the LORD remains contextually relevant for the contemporary church in integrating faith, worship, and social justice as an inseparable unity.